Supplementation with Hualian No. 4 wild bitter gourd (Momordica charantia Linn. var. abbreviata ser.) extract increases anti-fatigue activities and enhances exercise performance in mice - HSIAO, Chien-Yu (J Vet Med Sci, 2017)
Hualian No. 4 wild bitter gourd (WBG) is a specific vegetable cultivated by the Hualien District Agricultural Research and Extension Station in Taiwan. WBG is commonly consumed as a vegetable and used as a popular folk medicine. However, few studies have demonstrated the effects of WBG supplementation on exercise performance, physical fatigue and the biochemical profile. The purpose of this study was to evaluate the potential beneficial effects of WBG extract on fatigue and ergogenic functions following physiological challenge. Three groups of male ICR mice (n=8 per group) were orally administered 0, 1 or 2.5 g/kg/day of WBG for 4 weeks. They were respectively designated the vehicle, WBG-1X and WBG-2.5X groups. WBG significantly decreased body weight (BW) and epididymal fat pad (EFP) weight. Concerning physical performance, WBG supplementation dose-dependently increased grip strength and endurance swimming time. Concerning anti-fatigue activity, WBG decreased levels of serum lactate, ammonia, creatine kinase and blood urea nitrogen, and economized glucose metabolism after acute exercise challenge. Glycogen in the liver and gastrocnemius muscle dose-dependently increased with WBG treatment. Concerning the biochemical profile, WBG treatment significantly decreased alanine aminotransferase (ALT), blood urea nitrogen (BUN) and urea acid (UA), and increased total protein (TP). Therefore, 4-week supplementation with WBG may decrease white adipose weight, enhance energy economy, increase glycogen storage to enhance exercise performance and reduce fatigue.